Characteristics And Comorbidities In Patients With Urinary Tract Infections (UTI) - Christian Ronald Tanggo; Kezia Desideria Bontong; Jumaini Andriana Sihombing (CV. AFDIFAL MAJU BERKAH, 2026)
Urinary tract infection (UTI) is a common urogenital infection in both community and hospital settings, most frequently caused by Escherichia coli. In Indonesia, UTIs are estimated to reach 90–100 cases per 100,000 population annually and occur more often in females due to a shorter urethra that facilitates microbial entry. This study aimed to describe UTI case characteristics by age, sex, hypertension, diabetes mellitus, recurrent UTI history, and clinical manifestations at Universitas Kristen Indonesia Hospital during 2020–2021. A descriptive design was applied using secondary data from medical records. A total of 102 patients met the inclusion and exclusion criteria. The highest proportion of cases occurred in the 22–59-year age group (53 patients; 52.0%). Female patients predominated (62; 60.8%). Hypertension was identified in 45 patients (44.1%) and diabetes mellitus in 25 (24.5%). Recurrent UTIs were found in 53 patients (52.0%). Dysuria was the most frequent clinical manifestation (81; 79.4%). These findings indicate that UTIs at this hospital mostly affected adult females and were commonly accompanied by hypertension and recurrent infection, with dysuria as the leading symptom.